Slope Stability Analysis Using Limit Equilibrium and Numerical Modeling - Bagaskoro, Muhamad Nur; Mulenga, François K.; Yu, Hai-Sui (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2024)
Slope stability analysis is a fundamental aspect of geotechnical engineering due to its direct implications for infrastructure safety, mining operations, and disaster mitigation. Traditional analytical approaches, particularly the Limit Equilibrium Method (LEM), have been widely applied owing to their simplicity and clear mechanical interpretation. However, the increasing complexity of slope geometries, heterogeneous material conditions, and hydro-mechanical interactions necessitates the integration of numerical modeling techniques such as the Finite Element Method (FEM). This study presents a comprehensive slope stability analysis by systematically integrating LEM and FEM to evaluate safety factors, failure mechanisms, and critical slip surfaces. The research employs Bishop and Janbu methods within the LEM framework and the Shear Strength Reduction technique in FEM-based numerical simulations. Results demonstrate strong consistency between the two methods, with safety factor deviations generally within 1–3%, confirming findings reported in previous studies. FEM provides enhanced insight into stress redistribution, plastic zone development, and progressive failure behavior, which cannot be fully captured by conventional LEM. The study concludes that a hybrid analytical–numerical approach significantly improves reliability in slope stability assessment, particularly for complex geological and loading conditions. This research contributes to methodological refinement and offers practical guidance for slope design in civil and mining engineering applications.